The Effect of the Use of Personal Protective Equipment (PPE) and Automotive Workshop Conditions on the Safety of Motorcycle Engine Maintenance Laboratory Practices at AAG Adisutjipto Aviation Vocational School - Muchlis Dwi Prayoga; Widodo Widodo; Arif Bintoro Johan (Universitas Sultan Ageng Tirtayasa, 2026)
This study examines the influence of personal protective equipment (PPE) use and workshop conditions on the safety of motorcycle engine maintenance practicums at SMK Penerbangan AAG Adisutjipto. A quantitative approach with a correlational design was employed involving 41 grade X and XI Motorcycle Engineering students selected through total sampling. Data were collected using a validated questionnaire and analyzed using multiple linear regression to determine both partial and simultaneous effects of the independent variables. The findings indicate that PPE use and workshop conditions have a positive and significant contribution to practicum safety. Proper workshop facilities create a safe learning environment, while consistent PPE usage reduces accident risks during practical activities. These results highlight the importance of implementing occupational health and safety standards and strengthening students’ safety awareness in vocational education. The study provides practical recommendations for improving safety implementation and enhancing the quality of vocational learning practices.